Mass media coverage and vaccination uptake: Evidence from the demand for meningococcal vaccinations in Hungary - Anikó Bíró; Ágnes Szabó-Morvai (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2020)
We estimate the effect of mass media coverage of the meningococcal disease on the uptake of meningococcal vaccinations in Hungary. Our analysis is based on administrative county-level data on vaccination purchases linked to indicators of media coverage of the meningococcal disease and to administrative records of disease incidence. Using geographical and time variations in these indicators, our fixed effects estimates indicate a strong positive effect of mass media coverage of the disease on the rate of vaccination with all types of the meningococcal vaccine. At the same time, we do not find evidence that disease incidence itself has a positive impact on vaccination. These findings are broadly in line with imperfect information and the principles of bounded rationality and highlight the responsibility of mass media in influencing health-related behaviours.
Keywords: I12; I18; 330; vaccination; meningitis; mass media; imperfect information; bounded rationality